An ex vivo human skin model for studying skin barrier repair. Issue 1 (8th December 2014) - Danso, Mogbekeloluwa O.; Berkers, Tineke; Mieremet, Arnout; Hausil, Farzia; Bouwstra, Joke A.
Abstract In the studies described in this study, we introduce a novel ex vivo human skin barrier repair model. To develop this, we removed the upper layer of the skin, the stratum corneum (SC) by a reproducible cyanoacrylate stripping technique. After stripping the explants, they were cultured in vitro to allow the regeneration of the SC. We selected two culture temperatures 32°C and 37°C and a period of either 4 or 8 days. After 8 days of culture, the explant generated SC at a similar thickness compared to native human SC. At 37°C, the early and late epidermal differentiation programmes were executed comparably to native human skin with the exception of the barrier protein involucrin. At 32°C, early differentiation was delayed, but the terminal differentiation proteins were expressed as in stripped explants cultured at 37°C. Regarding the barrier properties, the SC lateral lipid organization was mainly hexagonal in the regenerated SC, whereas the lipids in native human SC adopt a more dense orthorhombic organization. In addition, the ceramide levels were higher in the cultured explants at 32°C and 37°C than in native human SC. In conclusion, we selected the stripped ex vivo skin model cultured at 37°C as a candidate model to study skin barrier repair because epidermal and SC characteristics mimic more closely the native human skin than the ex vivo skin model cultured at 32°C. Potentially, this model can be used for testing formulations for skin barrier repair.